Estimation of intrinsic water-use efficiency from δ13C signature of C3 leaves: Assumptions and uncertainty - Ma, Wei Ting; Yu, Yong Zhi; Wang, Xuming; Gong, Xiao Ying (Frontiers in Plant Science, 2023)
Carbon isotope composition (δ13C) has been widely used to estimate intrinsic water-use efficiency (iWUE) of plants in ecosystems around the world, providing an ultimate record of the functional response of plants to climate change. This approach relies on established relationships between leaf gas exchange and isotopic discrimination, which are reflected in different formulations of 13C-based iWUE models. In current literature, most studies have utilized the simple, linear equation of photosynthesis discrimination to estimate iWUE. However, recent studies demonstrated that using this linear model for quantitative studies of iWUE could be problematic. Despite these progresses, there is a scarcity of review papers that have comprehensively reviewed the theoretical basis, assumptions, and uncertainty of 13C-based iWUE models. Here, we 1) present the theoretical basis of 13C-based iWUE models: the classical model (iWUEsim), the comprehensive model (iWUEcom), and the model incorporating mesophyll conductance (iWUEmes); 2) discuss the limitations of the widely used iWUEsim model; 3) and make suggestions on the application of the iWUEmes model. Finally, we suggest that mechanistic understanding on mesophyll conductance associated effects and post-photosynthetic fractionation are the bottlenecks for improving the 13C-based estimation of iWUE.